The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/s19224903
|View full text |Cite
|
Sign up to set email alerts
|

Flexible UHF RFID Tag for Blood Tubes Monitoring

Abstract: Low-cost and flexible radio frequency identification (RFID) tag for automatic identification, tracking, and monitoring of blood products is in great demand by the healthcare industry. A robust performance to meet security and traceability requirements in the different blood sample collection and analysis centers is also required. In this paper, a novel low-cost and flexible passive RFID tag is presented for blood sample collection tubes. The tag antenna is based on two compact symmetrical capacitive structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Read Range Antenna s Area . (6) The performance of the proposed tag is compared to state-of-art RFID antennas and tags in Table 2. It can be observed that the proposed antenna achieves the highest FoM due to its compact size, while not compromising on the read range.…”
Section: Fom =mentioning
confidence: 99%
See 1 more Smart Citation
“…Read Range Antenna s Area . (6) The performance of the proposed tag is compared to state-of-art RFID antennas and tags in Table 2. It can be observed that the proposed antenna achieves the highest FoM due to its compact size, while not compromising on the read range.…”
Section: Fom =mentioning
confidence: 99%
“…Radio Frequency Identification (RFID) has been widely adopted as a communication and identification standard for low-cost distributed IoT systems [3][4][5][6][7]. UHF RFID, utilizing impedance-matched radiative antennas and passive RFID integrated circuits (ICs) enables read-range ranges in excess of few meters [3].…”
Section: Introductionmentioning
confidence: 99%
“…Various flexible wearable antenna sensors are implemented on different types of materials such as Kapton polyimide [ 92 ], cellulose filter paper [ 93 ], polydimethylsiloxane (PDMS) film [ 94 ], and graphene film (FGF) [ 95 ]. These materials are being applied as promising candidates for innovative flexible antenna sensors.…”
Section: Flexible Wearable Antenna Sensormentioning
confidence: 99%
“…Many radio frequency identification (RFID) tag antennas for ultra‐high frequency (UHF) band have been designed in the previous work 1‐5 . With these designs, some of the tag antennas can be mounted on metallic surfaces directly, 6,7 other reported designs can work on the human body, organs, blood bag and water‐filled containers 8‐11 . Some designs can be attached to a variety of object surfaces that have the multi‐usage function, as reported in Reference 12.…”
Section: Introductionmentioning
confidence: 99%
“…containers. [8][9][10][11] Some designs can be attached to a variety of object surfaces that have the multi-usage function, as reported in Reference 12. Besides, due to restriction on the available bands for UHF RFID in different countries and regions, some dual-band [13][14][15] or wideband [16][17][18] tag antennas have been designed.…”
mentioning
confidence: 99%